2009
DOI: 10.3109/17538150903359030
|View full text |Cite
|
Sign up to set email alerts
|

The role of quality tools in assessing reliability of the Internet for health information

Abstract: The Internet has made it possible for patients and their families to access vast quantities of information that previously would have been difficult for anyone but a physician or librarian to obtain. Health information websites, however, are recognised to differ widely in quality and reliability of their content. This has led to the development of various codes of conduct or quality rating tools to assess the quality of health websites. However, the validity and reliability of these quality tools and their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…[21][22][23] Several Internet tools and scoring systems have been used to assess the quality of health Web sites, but none has proven credibility to reliably judge transplant Web sites. 24 Rather than relying on kitemarks, clinicians might usefully take more interest in filling the gaps in validity and accuracy of information available on the Internet about complex topics like transplantation. Clinicians should also recommend authenticated Web sites to their patients, which can help patients by saving time.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Several Internet tools and scoring systems have been used to assess the quality of health Web sites, but none has proven credibility to reliably judge transplant Web sites. 24 Rather than relying on kitemarks, clinicians might usefully take more interest in filling the gaps in validity and accuracy of information available on the Internet about complex topics like transplantation. Clinicians should also recommend authenticated Web sites to their patients, which can help patients by saving time.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, both the tools and conduct codes are difficult to adopt by patients and often forgotten by providers, making necessary the investment to enhance their utilization in an easier way.…”
Section: Discussionmentioning
confidence: 99%
“…14 The trustfulness of information sources is crucial. 10,13 Brown-Johnson et al found that although most of population call on the internet and other electronic sources for tobacco-related health information, the highest trust was in interpersonal sources, especially providers and family & friends, far above the internet, media and social networks. 15 In the same sense, Weaver et al found the highest levels of trust in information about health effects of electronic nicotine delivery systems in the providers and official health institutes versus the manufacturers, commercial sellers and media.…”
Section: 13mentioning
confidence: 99%
“…Information that is publicly generated and made available on the Internet may be incorrect or misleading, and may cause harm (Hanif et al, 2009). Consequently, it is important that responsible healthcare professionals provide information, preferably from the actual transplant center.…”
mentioning
confidence: 99%